Teacher Education - New Perspectives 2021
DOI: 10.5772/intechopen.97085
|View full text |Cite
|
Sign up to set email alerts
|

Male Educator Recruitment in Early Childhood Centres: Implications for Teacher Education

Abstract: The absent male educators in the Early Childhood Development (ECD) programmes have created a gap in the momentum of success gained through fathers’ involvement in the early life of children. Worldwide, the gender imbalance trends in early childhood education and lower primary classes have been immemorial female skewed with men becoming extinct in the arena. Hitherto, copious studies testify of men’s involvement as fathers in young children’s early life as crucial for their social, emotional, and cognitive deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The imbalance towards females in ECE has been identified (Weaver-Hightower, 2011), with a shortage of male teachers in the US and Asian countries, such as Japan and South Korea (Wu, 2016), and they are also in the minority in China at just 2.22% (Yang, 2015). Policymakers in the UK (Lewis et al, 2022;Thornton & Bricheno, 2006) and other Western countries such as New Zealand (Livingstone, 2003), Australia (Martino & Kehler, 2006) and non-Western countries such as China and Nigeria (Mathwasa and Sibanda, 2021) are increasingly paying attention to the lack of male teachers in both kindergartens and primary schools.…”
Section: Introductionmentioning
confidence: 99%
“…The imbalance towards females in ECE has been identified (Weaver-Hightower, 2011), with a shortage of male teachers in the US and Asian countries, such as Japan and South Korea (Wu, 2016), and they are also in the minority in China at just 2.22% (Yang, 2015). Policymakers in the UK (Lewis et al, 2022;Thornton & Bricheno, 2006) and other Western countries such as New Zealand (Livingstone, 2003), Australia (Martino & Kehler, 2006) and non-Western countries such as China and Nigeria (Mathwasa and Sibanda, 2021) are increasingly paying attention to the lack of male teachers in both kindergartens and primary schools.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Trinidad and Tobago revealed that there are fewer male teachers in primary schools due to lower public confidence in males. The perception is that teaching in the primary phase is the role of the females since it is more about nurturing the child (Mathwasa & Sibanda, 2021). Similarly, Lingard (2018) reported that in the Central African Republic, females dominate the primary phase.…”
Section: Introductionmentioning
confidence: 99%